Carbon membrane technology : fundamentals and applications - He, Xuezhong (Chemical engineer); Kumakiri, Izumi (Boca Raton, FL : CRC Press, 2021)
"This book offers the condensed and interdisciplinary knowledge on carbon membranes, and provides the opportunity to the scientists who are working in the field of carbon membrane technology for gas and liquid separations to present, share, and discuss their contributions within the membrane community"--
OCLC-licensed vendor bibliographic record.
Keywords: Membrane separation; Membrane filters -- Materials; Carbon; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Earth Sciences / Geology; TECHNOLOGY / Environmental Engineering & Technology